Maternal Outcomes in Deliveries with Placenta Accreta Spectrum: A Systematic Review - Rizki Selly Apriliani; Suryane Sulistiana Susanti; Wiwit Kurniawati; Imami Nur Rachmawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Postpartum hemorrhage is a leading complication, causing approximately 75% of maternal deaths. Placenta accreta spectrum (PAS) is characterized by the abnormal invasion of placental trophoblasts into the uterine myometrium, increasing the risk of severe hemorrhage. Globally, PAS incidence has risen, ranging from 0.2% to 0.9% of all pregnancies, primarily due to the increasing number of cesarean deliveries. Other maternal outcomes can also occur in mothers with PAS cases. Objective: this systematic review aims to describe maternal outcomes in deliveries involving PAS. Method: this systematic review study uses the PRISMA guidelines for literature search through databases, including ScienceDirect, ProQuest, Wiley, and Taylor and Francis, focusing on cohort and case-control studies. Thirteen articles in English published between 2019–2024 were analyzed, with 2,455 for total samples. Results: the study identified maternal outcomes, including hemorrhage, organ injury, infections, thromboembolism, vesicovaginal fistula, intensive care admission, and maternal death, with hemorrhage being the most significant complication. Recommendation: Optimal PAS management requires a combination of technology-based strategies, multidisciplinary collaboration, and well-planned interventions to reduce maternal morbidity and mortality.